Solving Downgrade and DoS Attack Due to the Four Ways Handshake Vulnerabilities (WIFI) - Cyrille Clovis Tchouchoua Teyou; Pin Zhang (International Journal of Engineering and Management Research, 2018)
The growing volume of attacks on the Internet has increased the demand for more robust systems and sophisticated tools for vulnerability analysis, intrusion detection, forensic investigations, and possible responses. Current hacker tools and technologies warrant reengineering to address cyber crime and homeland security. The being aware of the flaws on a network is necessary to secure the information infrastructure by gathering network topology, intelligence, internal/external vulnerability analysis, and penetration testing. This paper has as main objective to minimize damages and preventing the attackers from exploiting weaknesses and vulnerabilities in the 4 ways handshake (WIFI). We equally present a detail study on various attacks and some solutions to avoid or prevent such attacks in WLAN.